ABOUT SOME PROBLEMS GEOMETRY OF FOOT DRAWING - A.V. Mastipanova (Academy of Cognitive and Natural Sciences, 2022)
The tasks of construction of geometrical elements by the division of corners are examined in the article. A method passed the tests on employment on drawing on the fine-art faculty of the Kryvoy Rog state pedagogical university.